Writing research proposals in the health sciences a step-by-step guide - Schneider, Zevia Merle; Fuller, Jeff 1952,- (Los Angeles SAGE, 2018)
This is your step-by-step guide on how to write successful research proposals in the health sciences, whether it is for a thesis or dissertation review committee, an ethical review committee or a grant funding committee. Using quantitative, qualitative, and mixed research approaches, follow the journey of Liang and Natasha, two fictional researchers who will help you complete your proposal alongside reading the chapters. This practical guide includes top tips from the authors, read-reflect-respond activities and examples of project plans to equip you with all the tools you need to succeed with your research proposal. -- Provided by publisher.
Step One: Proposal preparation -- Step Two: Background and justification for the study -- Step Three: Research approach and design -- Step Four: Capturing attention- abstract, title and significance -- Step Five: Feasibility, track record and teams -- Step Six: Writing an ethics proposal -- Step Seven: Writing a funding proposal.
Includes bibliographical references and index.
Keywords: Proposal writing in medicine